Ancaman Pidana Mati Bagi Pelaku Tindak Pidana Begal Sebagai Solusi Mengurangi Tingkat Kejahatan Begal di Kota Makassar - Hamzah, Hamzah (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2016)
Criminal robber today increasingly made public Makassar City can not perform its activities properly, because it always felt threatened by street actions of the perpetrators. From the research, the crime robber in Makassar more dominant influenced by the desire to emulate after watching a scene or event through electronic media TV has indirectly serving news or violent incidents that occurred in various parts of the country water. The spectacle results become negative for the development of child education which is precisely through such education the children will try to do and practice sees. In sociology called